QUIOSKE ARACNE: CALCULATION OF WIND LOADS ON A STRUCTURE IN BAMBOO UNCONVENTIONAL - BERALDO, ANTONIO; ALBIERO, DANIEL; MACIEL, ANTONIO JOSÉ DA SILVA (Revista Brasileira de Engenharia de Biossistemas, 2008)
This research work report a structural calculus of a bamboo kiosk. Structural components werepillars and beams of a bamboo specie Guadua angustifolia. Brazilian standard NBR 6123 – buildingwind loads evaluation was applied. For simplification, bamboo pillars were considered as pipeswith 12 cm in outer diameter and 3 cm wall thickness, the beams was considered as pipes of 7.5cm outer diameter and 2 cm thickness of wall, these elements were considered as intercalatedeach 25 cm by means a solid disc element simulating the knot effect. In this approaches acommercial software was employed for structural analyses. After data processing, Von Misesstress graph (principal stress composition, flexure and tri-dimensional torsion) and the maximumbending stress were obtained. The results show that the bamboo Aracne structure satisfactorilysupports the wind loads, as mean result the culms of specimen Guadua angustifolia reinforcedwith conventional concrete and steel bars CA50 support the forces applied for the wind, followingthe standard NBR6123.